The influence of financial and technological structure on eco-efficiency: an application of DDF bootstrapped framework in the Italian polluting industries. (21st October 2022) - Falavigna, Greta; Manello, Alessandro
In this paper, we estimate environmental corrected efficiency scores for a large sample of Italian firms operating in four different polluting industrial sectors subjected to the same European normative framework. Merging economic and emission data coming from reliable public sources, we measure overall performances through the non-parametric directional distance function and in order to improve the robustness of the results, we perform an extension of the bootstrap proposed for standard efficiency scores. Results are analysed through a truncated regression after testing for the validity of separability condition between input-output space and explanatory variables as well as in light of industrial specificity. Results show that both the financial structure and the technological status of the firms have a significant explanatory power in relation to environmental corrected efficiency scores. Policymakers should carefully consider both aspects as important issues for supporting sustainable practices.